Factors affecting poor nutritional status after small bowel resection in patients with Crohn disease. Issue 30 (July 2016) - Jang, Ki Ung; Yu, Chang Sik; Lim, Seok-Byung; Park, In Ja; Yoon, Yong Sik; Kim, Chan Wook; Lee, Jong Lyul; Yang, Suk-Kyun; Ye, Byong Duk; Kim, Jin Cheon
Abstract : Abstract: In Crohn disease, bowel-preserving surgery is necessary to prevent short bowel syndrome due to repeated operations. This study aimed to determine the remnant small bowel length cut-off and to evaluate the clinical factors related to nutritional status after small bowel resection in Crohn disease. We included 394 patients (69.3% male) who underwent small bowel resection for Crohn disease between 1991 and 2012. Patients who were classified as underweight (body mass index < 17.5) or at high risk of nutrition-related problems (modified nutritional risk index < 83.5) were regarded as having a poor nutritional status. Preliminary remnant small bowel length cut-offs were determined using receiver operating characteristic curves. Variables associated with poor nutritional status were assessed retrospectively using Student t tests, chi-squared tests, Fisher exact tests, and logistic regression analyses. The mean follow-up period was 52.9 months and the mean patient ages at the time of the last bowel surgery and last follow-up were 31.2 and 35.7 years, respectively. The mean remnant small bowel length was 331.8 cm. Forty-three patients (10.9%) underwent ileostomy, 309 (78.4%) underwent combined small bowel and colon resection, 111 (28.2%) had currently active disease, and 105 (26.6%) underwent at least 2 operations for recurrent disease. The mean body mass index and modified nutritional risk index were 20.6 and 100.8, respectively. The independent factors affecting underweight status were remnant small bowel length ⩽240 cm (odds ratio: 4.84, P < 0.001), ileostomy (odds ratio: 4.70, P < 0.001), and currently active disease (odds ratio: 4.16, P < 0.001). The independent factors affecting high nutritional risk were remnant small bowel length ⩽230 cm (odds ratio: 2.84, P = 0.012), presence of ileostomy (odds ratio: 3.36, P = 0.025), and currently active disease (odds ratio: 4.90, P < 0.001). Currently active disease, ileostomy, and remnant small bowel length ⩽230 cm are risk factors affecting the poor nutritional status of patients with Crohn disease after small bowel resection.